2018
DOI: 10.1111/dom.13442
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐rapid BioChaperone Lispro improves postprandial blood glucose excursions vs insulin lispro in a 14‐day crossover treatment study in people with type 1 diabetes

Abstract: BCLIS was well tolerated and safe over 14 days of treatment and significantly improved postprandial BG vs LIS when administered at mealtime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 3 publications
(5 reference statements)
0
30
0
1
Order By: Relevance
“…A new generation of ultra‐fast‐acting insulins, such as BioChaperone Lispro, treprostinil lispro and fast‐acting insulin aspart (faster aspart), is under development. Faster aspart is the first of these to be approved for pump use in adults with T1D and type 2 diabetes (T2D) and it is now available in several countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new generation of ultra‐fast‐acting insulins, such as BioChaperone Lispro, treprostinil lispro and fast‐acting insulin aspart (faster aspart), is under development. Faster aspart is the first of these to be approved for pump use in adults with T1D and type 2 diabetes (T2D) and it is now available in several countries.…”
Section: Introductionmentioning
confidence: 99%
“…15 Current rapid-acting insulin analogues (RAIAs)insulin aspart (IAsp), insulin lispro and insulin glulisinehave faster absorption kinetics than regular human insulin; 16 however, post-prandial glucose (PPG) control with pump therapy remains limited by the pharmacokinetics of RAIAs. 17 A new generation of ultra-fast-acting insulins, such as BioChaperone Lispro, 18,19 treprostinil lispro 20 and fast-acting insulin aspart (faster aspart), is under development. Faster aspart is the first of these to be approved for pump use in adults with T1D and type 2 diabetes (T2D) and it is now available in several countries.…”
mentioning
confidence: 99%
“…Participants will receive single doses (0.15 U/kg) of BioChaperone Lispro, Fiasp, and NovoLog via pump on three separate visits. Previously, BioChaperone Lispro has demonstrated an accelerated insulin action profile versus traditional prandial insulins, both via syringes and pumps, and in patients with T1D and T2D . This study will show how Adocia's candidate compares with other ultrarapid acting insulins.…”
Section: Company Updatesmentioning
confidence: 88%
“…The majority of the faster aspart trials have been published, while results of the trials for ultra‐rapid lispro are currently only in abstract form . Two of the BioChaperone Lispro trials have been published with several trials reported as abstracts . Key findings from the completed trials are summarized below.…”
Section: Second Generation Rapid‐acting Insulin Analoguesmentioning
confidence: 99%